2006
DOI: 10.1038/sj.cdd.4401890
|View full text |Cite
|
Sign up to set email alerts
|

TIR, CARD and PYRIN: three domains for an antimicrobial triad

Abstract: Innate immunity to microorganisms in mammals has gained a substantial interest during the last decade. The discovery of the Toll-like receptor (TLR) family has allowed the identification of a class of membrane-spanning receptors dedicated to microbial sensing. TLRs transduce downstream signaling via their intracellular Toll-interleukin-1 receptor (TIR) domain. More recently, the role of intracellular microbial sensors has been uncovered. These molecules include the Nod-like receptors Nod1, Nod2, Ipaf and Nalps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(106 citation statements)
references
References 132 publications
3
97
0
6
Order By: Relevance
“…Most evidence reported so far argues for a critical role of these proteins in the activation of the NF-jB pathway [3]. In line with this assumption, we recently demonstrated that intraperitoneal injection of FK156 results in a strong and fast Nod1-dependent release of KC [14], the induction of which is mainly driven by NF-jB.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Most evidence reported so far argues for a critical role of these proteins in the activation of the NF-jB pathway [3]. In line with this assumption, we recently demonstrated that intraperitoneal injection of FK156 results in a strong and fast Nod1-dependent release of KC [14], the induction of which is mainly driven by NF-jB.…”
Section: Discussionsupporting
confidence: 68%
“…Members of this family also include NALP proteins, IPAF and NAIP, and recent evidence has demonstrated that some NLR serve as intracellular sensors of bacteria and/or danger signals [1][2][3]. The role of Nod1 and Nod2 as intracellular surveillance molecules implicated in the innate immune responses to bacteria has been demonstrated in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins named NOD-like receptors (NLRs) are intracellular sensors of pathogens and other stresses. 53,54 NLRs include proteins such as NOD1 and NOD2, that sense bacterial peptidoglycans and activate the kinase RIP2 and nuclear factor-kB, 55 and three subfamilies of proteins involved in the formation of caspase-1-activating complexes: NALPs, IPAF and NAIPs ( Figure 2). …”
Section: Activation Of Inflammatory Caspases: Inflammasomes and Othermentioning
confidence: 99%
“…Toll-like receptors (TLRs) recognize microbes either on the cell surface or on lysosome/endosome membranes, while pathogens that invade the cytosol are detected by cytoplasmic PRRs, including the Nucleotidebinding Oligomerization Domain-Leucine-Rich Repeat (NOD-LRR) proteins, Peptidoglycan Recognition Proteins (PGRP) and the caspase recruitment domain (CARD)-helicase proteins. [1][2][3][4][5][6] Recent studies suggest that PRRs may also recognize damage-associated molecular pattern molecules (DAMPs) from dying host cells 2 and may induce inflammatory responses in the absence of microbes. Thus, PRRs play a central role in host homeostasis by recognizing both exogenous pathogen-derived and endogenous danger signals.…”
Section: Introduction To Pattern Recognition Receptorsmentioning
confidence: 99%